Student Perspectives on the Existence of Pancasila Education Courses at Universitas PGRI Wiranegara - Roichanah Roichanah; Linda Ning Utami; Riskiyah Nur Aini (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
The existence of Pancasila education plays an important role in shaping character and identity. Pancasila education is one of the subjects expected to develop the character and national identity of students in Indonesia. The purpose of this research is to find out how students perceive the Pancasila education course, whether it is considered important or not, and whether they have a liking for it or not, especially for cross-major students of PPKn. This research adopts a qualitative method by interviewing several students. Based on the interview results, 85% stated that the existence of the Pancasila education course is considered important for shaping the nation's character. 10% of respondents consider this course to be quite important, while 5% stated that this course is less important due to its lack of relevance to their chosen major. From the results of this study, it is clear that PGRI Wiranegara University students generally view the Pancasila Education course as important and relevant. They feel that this course helps strengthen their understanding of national values and develops better character, although many of them hope that the learning could be more engaging. Therefore, this article will further discuss the students' perspectives on the importance of the Pancasila Education course at PGRI Wiranegara University